2013
DOI: 10.3906/tar-1211-15
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of essential oil of Prangos ferulacea (Umbelliferae) against Ephestia kuehniella (Lepidoptera: Pyralidae) and Trichogramma embryophagum (Hymenoptera: Trichogrammatidae)

Abstract: Essential oil vapors obtained by the hydrodistillation of Prangos ferulacea (Umbelliferae) were tested on the different stages of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) and egg parasitoid Trichogramma embryophagum Hartig (Hymenoptera: Trichogrammatidae). Extracts of the volatile fractions from P. ferulacea were analyzed by capillary gas chromatography-mass spectrometry. The major compound of the essential oil was detected as 2,3,6-trimethyl benzaldehyde (66.59%) and the minor compound was heneicos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The LC 50 and LC 99 values of the essential oil against the egg stages of E. kuehniella and T. embryophagum were 320.372-486.839 and 2.121-5.662 µL/L air, respectively. The results of this study indicated that essential oil of P. ferulacea should be used as a control agent against these pests for integrated pest management programs [79].…”
Section: Other Propertiesmentioning
confidence: 82%
“…The LC 50 and LC 99 values of the essential oil against the egg stages of E. kuehniella and T. embryophagum were 320.372-486.839 and 2.121-5.662 µL/L air, respectively. The results of this study indicated that essential oil of P. ferulacea should be used as a control agent against these pests for integrated pest management programs [79].…”
Section: Other Propertiesmentioning
confidence: 82%
“…Considerable variability in the chemical profiles of the essential oils of the populations of P. ferulacea of different geographical origin has been reported and recently reviewed [ 6 ]. In fact, for a Turkish accession of P. ferulacea , 2,3,6-trimethyl benzaldehyde was reported as the predominant constituent (66.59%) [ 34 ], whereas β -pinene (43.1%), α-pinene (22.1%) and δ -3-carene (16.9%), ( E )-caryophyllene (48.2%), α-humulene (10.3%) and spathulenol (9.4%), terpinolene (38.1–56.3%), α-pinene (57%), and α-pinene (36.6%) and β -pinene (31.1%), respectively were detected as volatile markers of different Iranian populations [ 6 ]. The chemical diversity between the different oils compared is linked to many factors, such as pedoclimatic conditions, including the climate, amount of rainfall, altitude, distance and effects of proximity to the sea and exposure to wind and sun.…”
Section: Resultsmentioning
confidence: 99%
“…Gözek (2007) demonstrated that adult and larval stages of Tribolium confusum Jaquelin Du Val, 1868 (Coleptera: Tenebrionidae) were the most tolerant stages to treatments of garlic essential oil. On the other hand, Sümer Ercan et al (2013) found that adult of Ephestia kuehniella Zeller, 1879 (Lepidoptera: Pyralidae) was the most sensitive stage to exposure of Prangos ferulaceae Lindl. essential oil.…”
Section: Discussionmentioning
confidence: 99%